2023
DOI: 10.1039/d2en01076c
|View full text |Cite
|
Sign up to set email alerts
|

A promising approach to an environmentally friendly pest management solution: nanocarrier-delivered dsRNA towards controlling the destructive invasive pest Tuta absoluta

Abstract: To develop an environmentally friendly pest controlling RNAi method for the destructive invasive pest Tuta absoluta, we analysed the binding ratio between the nanocarrier and dsRNA, performed morphological characterization, investigated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 84 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…12,18,19 The tomato leaf miner is another disease-causing insect, which can be decreased using nanobioconjugates as a remedy for the ailment. 20 3.1. Types of Nanomaterials and Their Conjugates Used.…”
Section: Nanomaterial-based Rnai Delivery For Pest and Crop Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…12,18,19 The tomato leaf miner is another disease-causing insect, which can be decreased using nanobioconjugates as a remedy for the ailment. 20 3.1. Types of Nanomaterials and Their Conjugates Used.…”
Section: Nanomaterial-based Rnai Delivery For Pest and Crop Managementmentioning
confidence: 99%
“…Per studies, it was observed that the nanocarrier mode of the RNAi gene dysregulating method to prevent pests and microbes like the African malaria mosquito, yellow fever mosquito, bean yellow mosaic virus, cucumber mosaic virus, Rhizoctonia solani , Fusarium oxysporum , Xanthomonas oryzae , and so on is a successful utilization. ,, The tomato leaf miner is another disease-causing insect, which can be decreased using nanobioconjugates as a remedy for the ailment …”
Section: Nanomaterial-based Rnai Delivery For Pest and Crop Managementmentioning
confidence: 99%
“…Thabet et al found that using SiO 2 NPs was superior in preventing the spread of the cowpea aphid, Aphis craccivora . The tomato leaf miner, an invasive pest Tuta absoluta, could be controlled using dsRNA–NP complexes after specific target dsRNA delivery was successfully mediated by chitosan and star polycation nanomaterials …”
Section: Introductionmentioning
confidence: 99%
“…14 The tomato leaf miner, an invasive pest Tuta absoluta, could be controlled using dsRNA− NP complexes after specific target dsRNA delivery was successfully mediated by chitosan and star polycation nanomaterials. 15 Generally, secondary metabolites are triggered in plants in response to abiotic (drought, light, salt) and biotic (pathogens) stress. 16 Low doses of NPs are now explored as safer and more relevant to the environment, but they have yet to garner as much attention as their higher counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation